La Notte - Michelangelo Antonioni (1961)
Giovanni, a successful writer, and his wife Lydia visit their friend Tommaso who is dying in hospital. After their visit Giovanni goes to a promotion party for his new book, Lydia visits their old living area of Milano. They meet back at home and decide to visit the party of a billionaire, who wants Giovanni to write a book about the history of his company. Both have flirts, and they both notice this fact. Lydia phones the hospital and is informed, that Tommaso is dead. In the morning he tells her husband that she doesn't love him anymore. Black and White Film.
Keywords: Drama